Evaluasi Daya Tarik Wisata di Kebun Raya Cibodas dalam Sudut Pandang Kualitas Visual - Santi Desiana Yulianti; Hanni Adriani; Ray March Syahadat (http://arl.faperta.ipb.ac.id/, 2020)
This research was motivated by the diversity of natural and artificial resources in Cibodas Botanical Garden which has a visual quality of landscape beauty that becomes a tourist attraction. This study aims to determine the value of visual quality of tourist attractions in Cibodas Botanical Garden. The method used was a quantitative descriptive approach. Data obtained from observation and literature study and distributing questionnaires to respondents using a sample of 100 people using the Scenic Beauty Estimation (SBE) method. The assessment was carried out on thirteen tourist attractions of Cibodas Botanical Garden which consisted of Decorative Garden Galleries, Sakura Gardens, Cibogo Waterfall, Ciismun Waterfall, Lumut and Amorphophalus Gardens, Greenhouses, Paku-pakuan Collection, Guest House, Rhododendron Garden, Medicinal Plants Collection, Liana Garden, Large Pond and Semar Pocket House. The total visual assessed was 26 landscapes. Based on the assessment obtained, it shows the tourist attraction landscape that gets the highest visual quality (SBE) value, namely Landscape 12 with a value of 100.53, which is included in the classification of